The Relationship Between Blood Glucose Levels and Sleep Quality in Patients with Diabetes Mellitus - Anggrainy, Dian; Imam, Sentot; Ellina, Agusta Dian (GLOBAL HEALTH SCIENCE GROUP, 2025)
IGD patients’ dissatisfaction can occur if the service received does not meet patients’ expectations. Communication style and response time from medical and non-medical personnel are factors that can affect patients’ satisfaction. Objective: The objectives of this study are: 1) to determine the response time carried out by all officers in the Emergency Installation (IGD) at the Tugu Koja Regional General Hospital (RSUD) North Jakarta. 2) to determine the classification of response time of all officers in the Emergency Installation (IGD) at the RSUD Tugu Koja North Jakarta. 3) to find out the correlation of response time and patients’ satisfaction level in IGD at RSUD Tugu Koja North Jakarta. 4) to find out the communication style or method of all officers in IGD at RSUD North Jakarta. 5) to find out the correlation of the communication style of all officers in IGD and patients’ satisfaction level at RSUD Tugu Koja North Jakarta. Method: The subjects for this research are 175 IGD patients at RSUD Tugu Koja, North Jakarta. The sampling technique used is simple random sampling. The data collection method used is a questionnaire method aimed at IGD patients and medical and non-medical personnel. The validity test shows that all questionnaire items (Statements 1–4) have a sig. (2-tailed) value < 0.05, confirming their validity. The reliability test yields a Cronbach’s Alpha of 1.000, indicating excellent consistency. The data analysis technique used is Rank Spearman correlation. Results; Based on the results of the Spearman Rank test, it is found that there is a correlation between Response Time (X1) and Patients’ Satisfaction Level (Y). This is known from the sig. (2- tailed) value of 0.000 less than 0.05. However, Communication Style (X2) has no correlation with Patients’ Satisfaction Level (Y). This is known from the sig. (2-tailed) value of 0.222 which is more than 0.005. Conclusion: The study concludes that Response Time (X1) is significantly correlated with Patients' Satisfaction Level (Y), while Communication Style (X2) is not.